La vorágine - Rivera, José Eustasio, 1888-1928 (Editorial Oveja Negra, 1983)
Relates the adventures of Arturo Cova, a hot-headed proud chauvinist and his lover Alicia, as they elope from Bogotá, through the flatlands and later, escaping from criminal misgivings, through the tropical jungles of Colombia.